Letter from the associated editor - Aparicio de Castro, Gloria (Journal of Management and Business Education, 2020)
In this letter, the number 3 of 2020 of the Journal of Management and Business Education is introduced. A brilliant article and a suggestive line of research by Professor Enrique Bigne head the number. His work introduces us to a new perspective, current, and with a great projection of the future, which is the necessary customization of the teaching-learning process in Business and Management, assisted by technology and the constant innovations in teaching and learning. In addition, the number includes a relevant contribution by the professors of the University of the Basque Country UPV-EHU, with its IKASEKIN model, formulated as an integral learning for the development of innovative capacity, and which received the Educational Innovation Award of XXXIII AEDEM Annual Congress, held in June 2019 in Seville. Other interesting contributions included in the number refer to the implications of new methodological tools that increasingly appear as protagonists in our classrooms, such as gamification or interactive digital applications to maintain attention and the motivation of the students in their learning.